Ética, educação e experiência formativa na temporalidade do presente - Ramos, Estéfani Dutra [UNESP] (2014)
This research has an objective think the subject of experience linked to education while degree´s space for the skill to experience. The importance of our research subject justify by present diagnoses about experience impoverishment consequent of advancement of technique and capitalism, what subject the man to new forms of dominate, blocking him to stablished a degree of sense with the tradition and,therefore, becoming him unable of tell and means his experiences. This diagnose tought range of education and culture makes prevailing at education a know-how in contraposition to know-expressing by experience of education. Our intention is reflect about a education that care impoverishment experience in a time marked by technological speech and a temporariness ruled by market logical. We´re doing this turning to the idea to an education poetical and the historical testimonial thinking for philosophers as Fernando Bárcena and Seligman-Silva in a intention of analysis the importance of a language of experience in a educational scene, as element for thinking in animation our experience in this space. Because of this, our trajectory is planned in na analysis of experience´s idea and “impoverishment of our experience” , tought by Walter Benjamin, mainly in essays “Experience and Poverty.”, The Storyteller...